Harnessing ethical leadership and Islamic workplace spirituality to boost workplace engagement - Desastra, Yolla Zelika; Nasrulloh, Lisa Fahri; Pariyanti, Eka; H, Dede (Institute of Computer Science (IOCS), 2024)
The research was conducted with the aim of investigating the relationship between ethical leadership, Islamic workplace spirituality, and employee engagement in pesantrens in Bandar Sribhawono. The research employed a quantitative approach, where data was collected through questionnaires distributed both offline and online to pesantren managers. The collected data was then analyzed using the Statistical Package for the Social Sciences (SPSS) software with regression analysis techniques. The findings indicate that ethical leadership significantly correlates with employee engagement in pesantrens. Islamic workplace spirituality also shows a positive relationship with employee engagement. Additionally, there is a positive relationship between ethical leadership and Islamic workplace spirituality. These findings provide insight that ethical and spiritual values play crucial roles in enhancing employee engagement in pesantrens, with implications for pesantren management and human resource development in this context